1998
DOI: 10.5089/9781451844351.001
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Sustainability with Non-Renewable Resources

Abstract: This paper assesses sustainable fiscal behavior in an economy where wealth is derived predominantly from a non-renewable resource. It explores the issue in a simple dynamic framework that highlights the structural weaknesses in the underlying budgetary position, _ takes into account the rate of depletion of a country's natural resource base, and examines the impact of changes in a country's terms of trade. An alternative indicator of fiscal sustainability is derived, and the principal factors determining susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 9 publications
0
14
0
3
Order By: Relevance
“…Lastly, noncausality arises in a model in which tax and spending levels are determined by policymakers by targeting specific shares of GDP (Hoover and Sheffrin, 1992). Chalk (1998) has shown that oil-dependent countries can enjoy resource-related revenues that serve as a substitute for fiscal reform when the country's terms of trade are favorable. Arguably, government overspending can be financed through income 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 OIL DUTIES TAX REVENUE % of GDP Figure 2.…”
Section: The Connection Between Oil Revenues Taxes Government Spendmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, noncausality arises in a model in which tax and spending levels are determined by policymakers by targeting specific shares of GDP (Hoover and Sheffrin, 1992). Chalk (1998) has shown that oil-dependent countries can enjoy resource-related revenues that serve as a substitute for fiscal reform when the country's terms of trade are favorable. Arguably, government overspending can be financed through income 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 OIL DUTIES TAX REVENUE % of GDP Figure 2.…”
Section: The Connection Between Oil Revenues Taxes Government Spendmentioning
confidence: 99%
“…The analysis of the linkage between government revenues and expenditures is much more complex if taxation is not the only relevant source of public sector revenue. Chalk (1998) has shown that a country with a sizeable nonrenewable resource endowment (e.g., oil) can enjoy resource-related revenues that serve as a substitute for fiscal reform when the country's terms of trade are favorable (Gelb, 1988). Supposedly, government overspending can be financed through income generated by the appreciative resource endowment.…”
Section: Introductionmentioning
confidence: 99%
“…The second strand of studies tends to investigate the optimal fiscal policy for oil-exporting countries, while the third on the other hand includes studies whose concerns are on how fiscal activities or variables in such economy respond to the changes in oil prices. Quite a number of studies have examined the optimal fiscal policy for oil-exporting countries (see, [9,10,11,12,13,14,15,16]).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Several empirical papers address fiscal sustainability in small oil exporting countries: Tersman (1991), Liuksila et al. (1994), Bascand and Razin (1997), Chalk (1998), Barnett and Ossowski (2002), Davoodi (2002), Baunsgaard (2003) and IMF (2003). These authors all use variants of the PI approach, which are expounded below.…”
Section: Fiscal Sustainability and Managing Oil Price Uncertaintymentioning
confidence: 99%